Guide to health workforce development in post-conflict environments (WHO GenevaCH, 2005)
Deals with the importance and issues of human resource development in post-conflict country settings. Focuses on ways of achieving a balance and comprehensive approach to human resource development within the context and constraints of post-conflict reconstruction. Covers the different components of human resource development, identifying the key steps and related questions that may need to be considered and addressed within the context of the individual country. Highlights opportunities and potential options, and gives examples of tools that have proved to be of use in different posts-conflict situations.
Keywords: HEALTH PERSONNEL